2022
DOI: 10.1097/01.ccm.0000909544.54572.65
|View full text |Cite
|
Sign up to set email alerts
|

954: Prone Ventilation in Intubated Covid-19 Patients: Systematic Review and Meta-Analysis

Abstract: INTRODUCTION:Prone ventilation is a well-established strategy in patients with severe ARDS as it has been shown to improve survival and mortality. However, in intubated patients with COVID-19 pneumonia, the data are limited, with no substantial evidence supporting its use. This meta-analysis is the first to examine the mortality benefit of prone ventilation in intubated COVID-19 patients. METHODS:A systematic search according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This article was previously presented as a meeting abstract at the 2023 Society of Critical Care Congress on January 23, 2023 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article was previously presented as a meeting abstract at the 2023 Society of Critical Care Congress on January 23, 2023 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent meta-analysis of seven retrospective cohort studies including 5216 COVID-19 patients concluded that intensive care unit (ICU) mortality was higher in the prone position, while no significant differences were found in terms of cumulative or hospital mortality, length of stay in the ICU, and duration of mechanical ventilation between prone and supine positions. 2 In addition, there is evidence that the prone position may have several adverse side effects, some of which are clearly acknowledged (e.g., pressure ulcers, nerve injury, bleeding, displacement of medical devices, etc. ), 3 while others are often overlooked.…”
mentioning
confidence: 99%